Evaluasi implementasi COSO Internal Control pada siklus penjualan dan penagihan UMKM Pisang Kipas - Allo Saputra; Lolita Faraknimela; Putri Selvina; Nurul Fitriah Herpan; Putri Ainun Nur; Fina Ruzika Zaimar (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2026)
Internal control plays an important role in maintaining smooth sales and billing for micro, small, and medium enterprises. Weaknesses in controls can lead to uncollectible receivables, cash declines, and potential fraud. This study aims to evaluate the application of the Committee of Sponsoring Organizations of the Treadway Commission Internal Control Integrated Framework framework to the Pisang Kipas business in Makassar. The method used is qualitative with a case study design through observation and interviews, then the results are analyzed descriptively based on five internal control components. The novelty of this research lies in the application of the COSO framework to the sales and billing cycle in family-based micro-businesses. The results show that the implementation of controls is still informal and undocumented, with weaknesses in risk assessment, financial recording, and monitoring. The study recommends the implementation of simple procedures, daily cash recording, as well as further research on adaptive internal control models for micro enterprises.